The Use of Botulinum Toxin A in the Management of Trigeminal Neuralgia: a Systematic Literature Review - Anton Rubis; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this article is to systematically review the use, efficacy, differences between botulinum toxin type A doses and side effects of botulinum toxin type A therapy in patients with trigeminal neuralgia.